Investigation of anisogrid cylindrical shells for strength, stability and torsional rigidity - L. M. Kovalchuk; T. V. Burnysheva (Космические аппараты и технологии)
The article discusses anisogrid mesh shell structures made of composite materials. The purpose of the work is to investigate anisogrid shells for strength, stability and torsional stiffness. Based on the developed parametric finite element model of the initial design, a multifactorial computational experiment was conducted. The models were built in the ANSYS software package. Two approaches to modeling were considered: the construction of a shell by sequentially specifying families of edges and the allocation of a structural element of the shell with subsequent copying along the circumference. The least time-consuming and resource-intensive approach for a personal computer has been chosen. The analysis of the stress state of the initial mesh structure during torsion showed: spiral ribs with a slope to the left are compressed, with a slope to the right they stretch, annular ribs work for tension and compression. According to the results of the computational experiment, the dependences of the maximum longitudinal stresses in the ribs on the change in the angle of inclination of the spiral rib to the generatrix, the number of pairs of spiral ribs and the thickness of the rib structure were determined. The strength, stability and rigidity of structures under torsion were studied, taking into account changes in the parameters of the rib structure. As a result of the study, two of the most rigid, durable and stable structures were selected, in which two vertical structural elements were excluded. Thus, a new type of anisogrid cylindrical structure containing vertical sections was studied for strength, stability and rigidity.